Rozłóż na czynniki wielomiany:
a) x3+4x
b) x2-3x-4
c) 8x3-27
d) 3x3-2x2+3x-2
e) x6+7x3-8
f) x3-4x
g) 4x2-1
h) x3+27
i) x5-2x3-x2+2
j) 3x3-2x2-6x+4
k) x2-4x+4
l) 12x3-3x
m) x2(x-2)-3(x-2)
n) x4-5x2+4
o) x4-x3-2x2
Rozwiąż równanie:
a) x3-x2+x-1=0
b) x3+3x2-4x-12=0
c) 3x3-2x2-6x+4=0
d) x3-√2x2-2x+2√2=0
e) x3+x2-4x-4=0
f) 2x3+x2-2x-1=0
g) 2x3+x2=10x+5
h) x3-√3x2-√3x+3=0

2

Odpowiedzi

Najlepsza Odpowiedź!
2009-11-11T15:34:36+01:00
Równania:
a)x3-x2+x-1=0
3x-2x+x-1=0
2x=0+1
2x=1/:2
x=0,5

b)3x+6x-4x-12=0
5x=12/:5
x=12/5

c)9x-4x-6x+4=0
-x=-4/(-1)
x=4

d)3x-√4x-2x+2√2=0
3x-2x-2x+2√2=0
-x=2√2/:(-1)
x= -2√2

e)3x+2x-4x-4=0
x=4

f)6x+2x-2x-1=0
6x=1/:6
x=1/6

g)6x+2x=10x+5
8x-10x=5
-2x=5/:(-2)
x= -5/2

h)3x-√6x-√3x+3=0
3x-√3x+3=0

2009-11-11T15:40:19+01:00
A)x3-x2+x-1=0
3x-2x+x-1=0
2x=0+1
2x=1/:2
x=0,5

b)3x+6x-4x-12=0
5x=12/:5
x=12/5

c)9x-4x-6x+4=0
-x=-4/(-1)
x=4

d)3x-√4x-2x+2√2=0
3x-2x-2x+2√2=0
-x=2√2/:(-1)
x= -2√2

e)3x+2x-4x-4=0
x=4

f)6x+2x-2x-1=0
6x=1/:6
x=1/6

g)6x+2x=10x+5
8x-10x=5
-2x=5/:(-2)
x= -5/2

h)3x-√6x-√3x+3=0
3x-√3x+3=0


chyba tak mam nadzieje że dobrze;)